Uma abordagem experimental para o ensino do calor específico de materiais - Almeida, Valdiney Rodrigues de (2022)
The teacher of basic education encounters several difficulties to perform experimental activities of the concepts of Physics, from the lack of an adequate physical structure of the school, equipment, to the lack of adequate pedagogical guidance. The high school textbooks bring the finished physical concepts with the physical constants tabled, which are transmitted to the students without any context, being absorbed by the student without any meaning. That justifies the development of the project where the idea is to make available to the Physics teacher a manual that brings a step by step to the assembly and application of experiment with materials of easy access and of low cost for the determination of the specific heat of the water. The objective is to develop an educational product that allows the teacher to show to his students that behind the equations and physical constants found in textbooks, there is a whole physical context, and thus, enabling the formation of a critical citizen who can understand the concepts significantly. The Educational Product was applied in a state public school with a second grade high school class and followed a Teaching and Learning Sequence - TLS based on David Ausbel's Significant Learning Theory. The educational product was applied in three classes: remote class (had access to the educational product through remote classes), test class (had access to the educational product through face-to-face classes) and control class (the content was developed in a traditional way through in-person classes). Analyzing the average of the results of the remote class, a decrease in student performance is observed. Comparing the average of the results of the test and control groups, it is observed that the performance of the test group was better. After analyzing the results of the three groups, it can be said that remote classes were inefficient compared to on-site classes. It is also concluded that there was an improvement in the teaching of calorimetry with the development and application of the educational product.